Percutaneous Nephrolithotomy For Staghorn Stones: A Minimally Invasive Approach In A Region With Elevated Kidney Stone Risk - Putera, Dewa Gede Agung Sasmara; Ariandy, Zaky; Telussa, Arley Sadra (Universitas Nusa Cendana, 2025)
A 41-year-old male with a 2-month history of left-sided abdominal pain and renal stones was treated at Prof. W. Z. Johannes Hospital, East Nusa Tenggara, Indonesia. The patients’ primary drinking water sources were rivers and refillable bottles, which elevated the risk of kidney stones. Plain radiography and MSCT imaging revealed a 5 cm x 3.5 cm staghorn stone in the left kidney. Percutaneous nephrolithotomy (PCNL) was performed in the supine position using the C-arm. A nephroscope was inserted through a small incision to visualize and extract the stone. Post-extraction, C-arm imaging assessed the kidney, and a nephrostomy tube was placed for drainage. Staghorn stones are large, branched stones that occupy much of the renal pelvis or calyces. The European Association of Urology (EAU) recommends PCNL as the first-line treatment for staghorn stones due to its high efficacy and low morbidity. PCNL, a minimally invasive approach, offers high stone-free rates, up to 95%, making it effective for stones over 20 mm. The patient's successful outcome highlights the efficacy of PCNL in managing staghorn stones, especially in areas with a high risk of kidney stones due to poor water quality. Early diagnosis and treatment avert severe complications such as recurrent infections and urosepsis.